Synthesis of Vicinal Aminoalcohols via Stereoselective Aza-Wacker Cyclizations and Access to (−)-Acosamine via Redox Relay - Weinstein, Adam B. (2013)
Diastereoselective aza-Wacker cyclization of O-allyl hemiaminals under aerobic conditions enables efficient access to 1,2-aminoalcohol derivatives from allylic alcohols. The scope of this method is presented and its utility is highlighted in a streamlined synthesis of the biologically important aminosugar (–)-acosamine.